Psychiatry and Sports Medicine - Schorb A; Niebauer J; Aichhorn W; 3; Schiepek G; 3; Scherr J; Claussen MC; 6; 7 (Deutsche Zeitschrift für Sportmedizin)
Overtraining is characterized by a mismatch between exerted strain and exercise tolerance. Overtraining is generally not sufficiently feared nor is enough attention paid to its prevention. As a result, the first warning signals and symptoms are often either perceived too late or there is a delay in the correct interpretation of signs. This often leads to negative consequences over months, which, in turn, can lead to more frequent injuries as well as Depression. Due to the increasing professionalism and density of competition in competitive sports, overtraining occurs more frequently as athletes are left with a shorter period of time to recover. In order to treat overtraining, it is first necessary to identify the syndrome. Symptoms are often disregarded and trainers and athletes attempt to compensate for poor performance with excessive training. This leads to a vicious cycle with significant reduction of the overall performance of the athlete as a consequence. Psychological parameters can also be signs of non-func-tional overload. Examples include restlessness, irritability, emotional instability, recurring states of fear, emerging indifference or reduced performance motivation. However, disturbed cognitive processes as an impairment of central elements of movement control can also occur. As part of sports psychiatric support, conspicuous psychological parameters can be recorded and contextualised. The Synergetic Navigation System (SNS) is available for systematic recording and corresponding process management. The Synergetic Navigation System (SNS) can be used as an instrument for load, training and competition control to prevent non-functional overload and overtraining. It is also suitable for promoting performance and preventing injuries as well as stabilizing the psychological structure.Key Words:Mental Health Symptoms, Mental Disorders, Injury Prevention, Exercise Intolerance, Synergetic Navigation System (SNS)